Potensi Pengembangan Wakaf Uang di Kota Palembang (Preleminary Research) - M.Rusydi M.Rusydi (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2015)
According to the literature, cash waqf has a potency to eliminate poverty and toincrease quality of live for Indonesia’s population. But the question that arises is,why in reality the potency and beneficiary of cash waqf hasn’t been existed. Thisresearch aims is to describe the potency and beneficiary of cash waqf inPalembang. Since the data obtained is very limited, preliminary research wasconducted. It will argue that due to the indicators of Palembang economicsperformance, it could be appropriate basis to increase the potency of cash waqf inthe future.Key Words: Cash Waqf, Economic Performance, and the Potency of Cash Waqf